Are Pre-service Science Teachers' Ethical Views on Genetic Issues Affected by their Moral Values?. (13th May 2015) - Ceyhan, Busra; Sahin, Nurettin
Abstract: As teachers have an influential role on the lives of their students, the moral values they impart to their students will to a great extent determine the ethical decisions made by the students. The present study aimed to determine pre-service science teachers' ethical views and moral values in relation to some genetic issues and to determine the effect of their moral values on their ethical decisions. In order to collect the data in the current study, a questionnaire that included items related to genetic issues and the Ethical Position Scale were employed. A positive and significant correlation was found between the pre-service science teachers' ( N  = 255) total scores of their opinions about genetic applications or legal regulations and idealist (Pearson's r= 0.145, p = 0.05) or relativist (Pearson's r = 0.218, p  = 0.01) moral values. The female participants were found to be more idealistic than the male participants and were found to have a greater tendency to make ethical decisions (Mfemale  = 42.22,  Mmale  = 40.85, t(2, 193), p  < 0.05).